The ICT Antecedents and Sole Proprietary Practicing Audit Firms: A Quantitative Study - Mohammed Muneerali Thottoli (Australasian Accounting, Business and Finance Journal, 2022)
The main objective of this study is to investigate the mediating effect of Information Communication Technology (ICT) training on the linkage between ICT confidence, ICT challenges as antecedents of Sole Proprietary Practicing Audit Firms (SPPAFs) were the firms having lower than 100 clients. The study adopts a quantitative approach where a set of questionnaires were designed using a Likert scale to collect 165 usable data from auditors of SPPAFs in India. The data were analyzed using Smart PLS and SPSS statistical tools. The findings confirmed that ICT training mediates the linkages between ICT antecedents (ICT confidence and ICT challenges) and SPPAF. The conceptual model of the study can be useful to understand ICT antecedents of SPPAFs to increase the effectiveness of auditing. Hence, practicing auditors could realize ICT confidence and ICT challenges to improve firm effectiveness.
Keywords: ICT confidence; ICT challenges; ICT training; sole proprietary; practicing audit firms